2003
DOI: 10.1080/03079450310001610659
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism in mynah birds (Gracula religiosa)resembles human hereditary haemochromatosis

Abstract: Iron overload is a very frequent finding in several animal species and a genetic predisposition is suggested. In one of the most commonly reported species with susceptibility for iron overload (mynah bird), it was recently shown that the cause of this pathophysiology is high uptake and retention of dietary iron. Here we compare susceptible (mynahs) with non-susceptible avian species (chickens) by evaluating iron uptake at the intestinal absorptive cell level. Enterocytes from mynahs and chickens were isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…This supports the hypothesis that some species may have maximized their efficiency for iron uptake from low iron-content food in their natural habitat and cannot adapt to higher food iron content in captivity (Otten et al, 2001). Experimental studies of mynah birds and starlings suggest that the intestinal absorption of iron in birds is not as tightly regulated as it is in mammals and that susceptible species are unable adequately to down-modulate the uptake of iron to prevent iron storage disease (Ward et al, 1991;Mete et al, 2001Mete et al, , 2003. Mynah birds have greater intestinal uptake of iron compared with chickens and doves.…”
Section: Iron Storage In Birds: Malnutrition Orsupporting
confidence: 55%
See 2 more Smart Citations
“…This supports the hypothesis that some species may have maximized their efficiency for iron uptake from low iron-content food in their natural habitat and cannot adapt to higher food iron content in captivity (Otten et al, 2001). Experimental studies of mynah birds and starlings suggest that the intestinal absorption of iron in birds is not as tightly regulated as it is in mammals and that susceptible species are unable adequately to down-modulate the uptake of iron to prevent iron storage disease (Ward et al, 1991;Mete et al, 2001Mete et al, , 2003. Mynah birds have greater intestinal uptake of iron compared with chickens and doves.…”
Section: Iron Storage In Birds: Malnutrition Orsupporting
confidence: 55%
“…Mynah birds have greater intestinal uptake of iron compared with chickens and doves. Isolated mynah bird enterocytes showed considerably higher iron uptake compared with chicken enterocytes (Mete et al, 2003). The transporter affinity (Km) was similar for both species, but a three-fold higher uptake rate (V max ) was found, suggesting an increase in the number of iron transporters.…”
Section: Iron Storage In Birds: Malnutrition Ormentioning
confidence: 97%
See 1 more Smart Citation
“…It has been suggested that these species develop EIS under captive conditions due to a highly efficient intestinal iron absorption (Oglesbee et al, 1997;Lumeij, 1999). More recently, it has been shown that iron metabolism in hill mynahs (Gracula religiosa ) resembles that of human patients suffering from hereditary haemochromatosis (Mete et al, 2003), and that high levels of iron transporter proteins are expressed by the small intestine of these birds (Mete et al, 2005). In humans, EIS is strongly associated with DM (Wilson et al, 2003;Platis et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Mynahs are uncommonly susceptible to hepatic iron overload and have a defect in iron metabolism that resembles human hemochromatosis. 9 Although other animal species, such as New World Monkeys 10 and the black rhinoceros, 11 and some other bird families such as toucans and birds of paradise, 12 show a high prevalence of iron overload and progressive hepatic iron deposition, this is the most common metabolic disorder in the mynah, which is also the most frequently reported bird species to suffer from hemochromatosis. 13 What better crest for a common human liver disease could there be?…”
mentioning
confidence: 99%